2015
DOI: 10.1016/j.jcrc.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Delirium affects length of hospital stay after lung transplantation

Abstract: Background Delirium is relatively common following lung transplantation, although its prevalence and prognostic significance have not been systematically studied. The purpose of the present study was to examine pre-transplant predictors of delirium and the short-term impact of delirium on clinical outcomes among lung transplant recipients. Methods Participants underwent pre-transplant cognitive testing using the Repeatable Battery for the Assessment of Neuropsychological Status and the Trail Making Test. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 34 publications
3
32
2
4
Order By: Relevance
“…In the present sample, patients who experienced delirium showed lower neurocognitive performance compared with their nondelirious counterparts during follow-up assessments. We also previously noted that patients with delirium displayed poorer cognition at baseline and had longer hospitalization stays compared with patients without delirium (16).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the present sample, patients who experienced delirium showed lower neurocognitive performance compared with their nondelirious counterparts during follow-up assessments. We also previously noted that patients with delirium displayed poorer cognition at baseline and had longer hospitalization stays compared with patients without delirium (16).…”
Section: Discussionmentioning
confidence: 60%
“…In the days immediately after transplantation, patients were assessed daily for the presence and severity of postoperative delirium using two validated clinical instruments (16): the Confusion Assessment Method (CAM) and Delirium Rating Scale (DRS-98).…”
Section: Methodsmentioning
confidence: 99%
“…For example, mechanistic studies in animal models have demonstrated that experimental venous obstruction of the superior vena cava results in significant decreases in cerebral perfusion (43), which may be alleviated through either pharmacologic intervention or partial obstruction relief (44). These findings suggest that future studies may benefit from examining potential treatment strategies to mitigate superior vena cava obstruction during lung transplant, as the presence of postoperative delirium has been shown to improve clinical outcomes following hospitalization (6,8,45). It is also possible that elevated CVP resulted in increased edema or passive congestion, as elevated CVP has been associated with prolonged mechanical ventilation time and higher mortality among lung transplant recipients (46).…”
Section: Original Researchmentioning
confidence: 99%
“…Delirium is common following lung transplant and has been shown to be associated with poorer clinical outcomes (8) and future cognitive impairment (9). Several recent studies have suggested that poorer intraoperative hemodynamic function may be associated with adverse neurocognitive outcomes among patients undergoing surgical procedures requiring single-lung ventilation (10,11).…”
mentioning
confidence: 99%
“…The available data on delirium after lung transplantation is limited to a few small single center studies 9–11 . A retrospective study of 30 lung transplant recipients found that 73% of patients developed delirium in the first 2 weeks after transplantation 9 .…”
Section: Introductionmentioning
confidence: 99%